2023
DOI: 10.1021/acsanm.3c01556
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Trichromatic Fluorescent Carbon Dots for Printing and Imaging

Jie Li,
Guobin Xu,
YingMin Lu
et al.

Abstract: As a type of carbon-based nanomaterial, the most prominent feature of carbon dots (CDs) is their fluorescence properties. In this work, blue, green, and red water-dispersible CDs with trichromatic properties were prepared by a microwave method using corn starch, citric acid, p-phenylenediamine, and urea. The emission wavelengths of the CDs at the same excitation wavelength were 423, 524, and 621 nm, respectively. The morphological characteristics and optical properties of the three CDs were characterized, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…CDs were prepared by microwave method; 0.5 g of citric acid and 1.0 g of urea were fully dissolved in 20 mL of deionized water; they reacted under 700 W microwave irradiation for 5 min, cooled to room temperature, and centrifuged for 10 min twice. The supernatant was filtered by the 0.22 μm microporous membrane to obtain the aqueous solution of green fluorescent CDs, which was freeze-dried into a CD powder.…”
Section: Methodsmentioning
confidence: 99%
“…CDs were prepared by microwave method; 0.5 g of citric acid and 1.0 g of urea were fully dissolved in 20 mL of deionized water; they reacted under 700 W microwave irradiation for 5 min, cooled to room temperature, and centrifuged for 10 min twice. The supernatant was filtered by the 0.22 μm microporous membrane to obtain the aqueous solution of green fluorescent CDs, which was freeze-dried into a CD powder.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the content of pyridinic N in R-CDs (50.0%) doubled that of G-(22.3%) and B-CDs (24.5%, Table S4). Previous studies have shown that both graphitic N 43 and pyridinic N 46,47 could shift the emissions of C-dots to the red region. As such, the relatively richer presence of graphitic N and pyridinic N in R-CDs may be closely related to core-state emissions and responsible for their large conjugations and long wavelength emissions.…”
Section: Acsmentioning
confidence: 98%
“…The most common method for longer wavelength emission in near-infrared regions can be achieved by introducing heteroatoms into carbon lattices, resulting in defects in their framework. 18–22 Further, these red or orange emissive CDs are produced by multiple synthesis steps, 20 long reaction time 23,24 and high-temperature hydrothermal reaction 19,25 followed by complicated purification procedures, 26 such as silica-gel column chromatography 25,27 or dialysis. 9,28–30 Thus, orange–red emissive CDs with high emission intensity and excitation wavelengths of an independent nature in near-infrared regions without further post-purification methods are still highly desired.…”
Section: Introductionmentioning
confidence: 99%